Teachers’ and Students’ Perceptions About The Role Of Technology In Learning English At SMAN 3 Bukittinggi - Natalia, Melisa; Roza, Veni; Melani, Melyann; Syafitri, Widya (Journal of Educational Management and Strategy, 2023)
The role of technology in learning English has become a matter of whether it plays important role or not. The problem in this research was that the perception between teachers and students about the role of technology in learning English varied. This research aims to determine how teachers’ and students’ perceptions about the role of technology in learning English at SMAN 3 Bukittinggi. The researcher wanted to examine whether the perception of teachers and students were positive or not. The type of research used by the researcher was descriptive quantitative, utilized a questionnaire as an instrument. The population in this research were English teachers and eleventh grade of students at SMAN 3 Bukittinggi. The sample of this research were 4 (four) English teachers and class XI IPA 2 with the total of 36 (thirty-six) students. The researcher used cluster random sampling to determine the sample of students in this research. The researcher distributed a questionnaire to each sample, then collected the data. After that, the researcher identified the answers from the respondents and analyzed the data, then drew conclusions in the form of levels (categories). The results of this research, the perception of teachers and students about the role of technology in learning English is 88,03%. Based on the persentage result of this research indicated that teachers and students had very positive perception about the role of technology in learning English. Thus, the result of this research indicated that teachers and students feel that technology plays important role in learning English. Peran teknologi dalam pembelajaran bahasa Inggris telah menjadi persoalan apakah memainkan peran penting atau tidak. Masalah dalam penelitian ini yaitu persepsi antara guru dan siswa tentang peran teknologi dalam pembelajaran bahasa Inggris yang bervariasi. Penelitian ini bertujuan untuk mengetahui bagaimana persepsi guru dan siswa tentang peran teknologi dalam pembelajaran bahasa Inggris di SMAN 3 Bukittinggi. Peneliti ingin meneliti apakah persepsi guru dan siswa positif atau tidak.  Jenis penelitian yang digunakan peneliti adalah deskriptif kuantitatif, dengan menggunakan angket sebagai instrumen. Populasi pada penelitian ini adalah guru bahasa Inggris dan siswa kelas sebelas di SMAN 3 Bukittinggi. Sampel penelitian ini adalah 4 guru bahasa Inggris dan kelas XI IPA 2 dengan berjumlah 36 siswa. Peneliti menggunakan cluster random sampling untuk menentukan sampel siswa dalam penelitian ini. Peneliti menyebarkan angket kepada setiap sampel, lalu mengumpulkan datanya. Setelah itu, peneliti mengindentifikasi jawaban dari responden dan menganalisa data, lalu menarik kesimpulan dalam bentuk tingkatan level (kategori).  Hasil dari penelitian ini, persepsi guru dan siswa tentang peran teknologi dalam pembelajaran bahasa Inggris adalah 88,03%. Berdasarkan hasil persentase dari penelitian ini menunjukkan bahwa guru dan siswa memiliki persepsi yang sangat positif tentang peran teknologi dalam pembelajaran bahasa Inggris. Dengan demikian, hasil dari penelitian ini menunjukkan bahwa guru dan siswa merasa teknologi memainkan peran penting dalam pembelajaran bahasa Inggris.